Strategi Komunikasi Persuasif Komunitas Sobat Literasi Jalanan Palembang Dalam Meningkatkan Kesadaran Masyarakat Terhadap Minat Membaca Anak - Randa, Gusti; Murdiati, Eni; Muslimin, Muslimin (Jurnal Ilmu Sosial, Humaniora dan Seni, 2022)
This research is entitled "Persuasive Communication Strategy for Palembang's Street Literacy Friends Community in Raising Public Awareness of Children's Interest in Reading. The purpose of this study was to find out how the persuasive communication strategy of the Street Literacy Friends community was and to find out how the state of children's literacy was before and after the implementation of the Street Literacy Friends (SLJ) community persuasive communication strategy in increasing awareness of children's interest in reading. This study uses a qualitative method. Data collection techniques using observation, interviews and documentation. Data analysis techniques are data reduction, data display and drawing conclusions. The results of the research show that the persuasive communication strategy includes three stages, namely strategy formulation, strategy implementation, and strategy evaluation. The situation before the implementation of the persuasive communication strategy of public awareness was very far from caring, many of them chose to be indifferent because the community thought that street children were unruly and uneducated children, and access was quite difficult and the ups and downs of the enthusiasm of teachers in the SLJ Palembang community to educate child. The state of literacy for children, the community after the implementation of a persuasive communication strategy, the Street Literacy Friends of Palembang City became concerned and began to play an active role, seen from the enthusiasm of the Street Literacy Friends (SLJ) volunteers, which was very high compared to before.